Efficacy of a Novel Nematicidal Seed Treatment against Meloidogyne incognita on Cotton - Monfort, W S (Journal of nematology, 2006)
The efficacy of abamectin as a seed treatment for control of Meloidogyne incognita on cotton was evaluated in greenhouse, microplot, and field trials in 2002 and 2003. Treatments ranging from 0 to 100 g abamectin/100 kg seed were evaluated. In greenhouse tests 35 d after planting (DAP), plants from seed treated with abamectin were taller than plants from nontreated seed, and root galling severity and nematode reproduction were lower where treated seed were used. The number of second stage juveniles that had entered the roots of plants from seed treated with 100 g abamectin/kg seed was lower during the first 14 DAP than with nontreated seed. In microplots tests, seed treatment with abamectin and soil application of aldicarb at 840 g/kg of soil reduced the number of juveniles penetrating seedling roots during the first 14 DAP compared to the nontreated seedlings. In field plots, population densities of M. incognita were lower 14 DAP in plots that received seed treated with abamectin at 100 g/kg seed than where aldicarb (5.6 kg/ha) was applied at planting. Population densities were comparable for all treatments, including the nontreated controls, at both 21 DAP and harvest. Root galling severity did not differ among treatments at harvest